Pengaruh Media Sosial, Teman Sebaya, Gaya Hidup, dan Peran Keluarga Terhadap Perilaku Keuangan Mahasiswa Universitas Slamet Riyadi Surakarta - Anita Putri Hapsari; Babang Widarno (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
The purpose of this research is to analyze the influence of social media, peer groups, lifestyle, and family roles on the financial behavior of students at Slamet Riyadi University in Surakarta. This study uses a quantitative approach utilizing primary data as the main source. The research population includes all active students at Slamet Riyadi University from the 2021–2024 batch, totaling 7,316 individuals. The sample was determined using probability sampling techniques, resulting in 100 respondents as representatives. Data were collected through questionnaires, while the analysis was conducted using classical assumption tests, including tests for normality, multicollinearity, heteroscedasticity, and autocorrelation. Furthermore, hypothesis testing was performed using multiple linear regression, F-test, t-test, and the coefficient of determination (R²). The research results show that social media, lifestyle, and family roles have a significant positive influence on financial behavior. However, peers have a significant negative influence on students' financial behavior. Students need to improve financial literacy and manage their lifestyles proportionally with family support and the integration of financial education in the academic environment